2015
DOI: 10.1016/j.jngse.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of slippage and adsorption effects on gas transport in shale formations using the lattice Boltzmann method

Abstract: a b s t r a c tShale formations consist of numerous nanoscale pores within a range of 2 nme50 nm; the shale gas flow within this size range under typical shale reservoir pressure and temperature will fall into the slip flow or the transitional flow regime 0.001 < K n < 10. Besides nano-pores in shale, there exist a number of mesoscopic and macroscopic pores with size larger than 50 nm, and many micrometer fractures. Natural gas, mainly methane, flows through nanoscale pores, mesoscale, and macroscopic pores or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 41 publications
(76 reference statements)
0
29
0
Order By: Relevance
“…Therefore, the impact of this accommodation coefficient has been investigated in our previous work (Ning et al, 2015). It has been found that ϭ1.0 is a reasonable choice and it will be continuously used in this work.…”
Section: Effective Relaxation Timementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the impact of this accommodation coefficient has been investigated in our previous work (Ning et al, 2015). It has been found that ϭ1.0 is a reasonable choice and it will be continuously used in this work.…”
Section: Effective Relaxation Timementioning
confidence: 99%
“…The multiple-relaxation-time (generalized) LBM proposed by d' Humieres (1992) has been proved to be an effective LBM model for high Knudsen flows (Guo et al, 2008;Li et al, 2011;Ning et al, 2014;Ning et al, 2015). The generalized LBM relaxes various moments (i.e., density, energy, momentum, heat flux, viscous stress tensor, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the distinctive characteristics of shale rock formations is that typically more than 60 % of their porosity can be attributed to small nano-pores less than 30 nm in diameter [1][2][3][4][5][6][7][8][9][10]. As a result, these formations have extremely low permeability, typically of the order of magnitude of one hundred nanodarcies [11].…”
Section: Introductionmentioning
confidence: 99%
“…At the microscopic pore scale, the geometric structure of porous media is described in detail; while, at the mesoscopic REV scale, the geometric structure is simplified by an elementary cell using the volume-averaging method. Due to the briefness of boundary schemes to handle the complex morphology of porous matrix, a series of pore scale LB models have been proposed to study the adsorbate's mass transport and adsorption behaviors in the pore structures of porous media, which were constructed by the regular particles or the stochastic irregular solid matrix [21][22][23][24][25][26][27][28]. By using these LB simulations at the pore scale, the transient fluid velocity and the adsorbate concentration profiles in the pore structures were presented in detail, and the effect mechanism of pore structure characteristics on the dynamic adsorption performance was elaborated to provide a guidance for the design and optimization of adsorption systems in the micro-scale.…”
Section: Introductionmentioning
confidence: 99%